Perjanjian Kerja Sama Sumber Daya Minyak Bumi Dan Gas Bumi Di Perbatasan Maritim Dua Negara Berbeda Ditinjau Dari Hukum Laut Internasional - Putrawan, Fernando Indana; Kurnia, Ida (LPPM Universitas Ekasakti Padang, 2023)
Cooperation agreement plays a pivotal role in optimizing the cooperation of natural resources and promoting international collaboration in the context of petroleum and natural gas resources. Such agreements are also instrumental in maintaining positive relations among nations that share maritime boundaries. This paper delves into the position of cooperation agreements regarding petroleum and natural gas resources within the maritime territories of two different countries under international maritime law, and its impact on existing maritime boundary agreements. The research methodology employed here is normative legal research utilizing secondary and tertiary legal materials, including international regulations and scholarly literature. This study reveals that cooperation agreements are a form of bilateral agreement aimed at regulating collaboration in the exploitation of petroleum and natural gas resources. Within this framework, the involved nations have the authority to establish exploitation terms, as well as the allocation of rights and responsibilities. Various models of cooperation agreements are identified, such as the single-state model, two-state model, common entity model, and the trustee development model. The significance of cooperation agreements lies in strengthening inter-country collaboration for the exploitation of petroleum and natural gas resources within shared maritime regions.